Factors for the Creation of Technological Startups in Latin America - Vayas-Ortega, Germania (2024)
The changes produced in recent years have made innovation and technology play an important role in the growth of technological start-ups. Likewise, public policies have been developed that contribute to the development and strengthening of this business sector. The aim of the study is to analyze the incidence of institutional factors, education and innovation, in the generation of technological startups. The data analyzed comes from the Global Entrepreneurship Monitor, the Pearson Correlation statistical technique was applied. The results suggest that there is a direct relationship between the factors analyzed. In conclusion, the growth of this type of companies is still incipient in Latin American countries, however, there is significant growth of these in the region